The State of Open Data 2023 - Oefelein, Timon (Septentrio Conference Series, 2023)
The annual State of Open Data survey is a global and collaborative initiative aimed at understanding the dynamics of open data within the research community across different disciplines and regions. It seeks to uncover researchers' perspectives, behaviours, and the impact of data management on their work, ultimately contributing to the development of more effective data sharing practices that align with the evolving needs of the research community. Now in its eighth year, the 2023 survey findings, presented in this poster, shed light on the evolving landscape of research data sharing and emphasise the critical need for adaptable, nuanced approaches. This poster will give a preview of the 2023 results, pulling out some of the main findings and analysis of year-on-year trends, with key regional differences highlighted. One main theme to emerge is that a one size fits all approach for research data management does not work, rather there should be a move to a more nuanced strategy. Researchers across different disciplines and regions have unique needs, and their approaches to research data management vary significantly. This underscores the necessity of moving towards a more adaptable and nuanced data management strategies tailored to specific research contexts. The State of Open Data survey is conducted in partnership with Springer Nature, Figshare and Digital Science, enhancing the survey’s reach and impact and allowing for a more comprehensive analysis of the research data landscape.